Pancreatic β cells require NeuroD to achieve and maintain functional maturity - Gu, Chunyan (2010)
NeuroD, an insulin transactivator, is critical for development of the endocrine pancreas, and NeuroD mutations cause MODY6 in humans. To investigate the role of NeuroD in differentiated β cells, we generated mice in which neuroD is deleted in insulin-expressing cells. These mice exhibit severe glucose intolerance. Islets lacking NeuroD respond poorly to glucose and display a glucose metabolic profile similar to immature β cells, featuring increased expression of glycolytic genes and LDH-A, elevated basal insulin secretion and O(2) consumption, and overexpression of NPY. Moreover, the mutant islets appear to have defective K(ATP) channel-mediated insulin secretion. Unexpectedly, virtually all insulin in the mutant mice is derived from ins2, whereas ins1 expression is almost extinguished. Overall, these results indicate that NeuroD is required for β cell maturation and demonstrate the importance of NeuroD in the acquisition and maintenance of fully functional glucose responsive β cells.